2007
DOI: 10.1007/s10815-005-9002-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural sperm and aneuploidies studies in a case of spermatogenesis recovery after the use of androgenic anabolic steroids

Abstract: Purpose: Azoospermia may sometimes be related to the use of androgenic anabolic steroids. We report the case of an azoospermic man who had abused androgenic anabolic steroids and who recovered spermatogenesis six months after cessation of abuse and the administration of hormonal therapy. Methods: An azoospermic 34-year-old man came to Regional Referral Center for Male Infertility. The recovery of spermatogenesis was observed after the cessation of abuse of steroids and the administration of hormonal therapy. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 7 publications
0
7
1
2
Order By: Relevance
“…Immaturity, necrosis and apoptosis were assessed, and a high percentage of structurally normal spermatozoa were found, which showed the absence of a correlation between AAS and ultrastructural sperm changes. In contrast to these findings, FISH sperm analysis revealed XY and chromosomes 1 and 9 disomies, suggesting anomalies in the meiotic process and genetic damage among AAS users [18].…”
Section: The Impact Of Anabolic Steroids On Male Infertility: What Docontrasting
confidence: 69%
“…Immaturity, necrosis and apoptosis were assessed, and a high percentage of structurally normal spermatozoa were found, which showed the absence of a correlation between AAS and ultrastructural sperm changes. In contrast to these findings, FISH sperm analysis revealed XY and chromosomes 1 and 9 disomies, suggesting anomalies in the meiotic process and genetic damage among AAS users [18].…”
Section: The Impact Of Anabolic Steroids On Male Infertility: What Docontrasting
confidence: 69%
“…An increased risk of sperm aneuploidy was reported by Moretti et al . () that appeared to remain even after the discontinuation of the steroid abuse, indicating more permanent damage to the chromosome segregation machinery.…”
Section: Sperm Aneuploidy Predictive Factorsmentioning
confidence: 99%
“…In a study performed on power athletes, it was found that although spermatogenesis could be restored with hCG, sperm morphology and motility continued to be abnormal. Moretti et al 16 used fluorescent in-situ hybridisation for sperm chromosomal analysis after spermatogenesis recovery. A higher frequency of XY disomy and disomies between chromosomes 1 and 9 was identified.…”
Section: Anabolic Androgen Steroidsmentioning
confidence: 99%